Dietary Administration of Postbiotics from Vibrio proteolyticus DCF12.2 Enhanced Intestinal Integrity, Microbiota, and Immune Response in Juvenile Gilthead Seabream (Sparus aurata) - Olivia Pérez-Gómez; Sonia Rohra-Benítez; Marta Domínguez-Maqueda; Isabel M. Cerezo; Alba Galafat; Eduardo Martínez-Manzanares; Juan Miguel Mancera; Francisco Javier Alarcón-López; Jorge García-Márquez; Miguel Ángel Moriñigo; Salvador Arijo (Animals)
The use of postbiotics for dietary fortification in aquaculture is gaining increasing attention due to their potential immunomodulatory and gut health benefits. In this study, we evaluated the effects of postbiotics derived from Vibrio proteolyticus DCF12.2 on intestinal histology, microbiota composition, and the expression of genes related to epithelial integrity and inflammation in juvenile gilthead seabream (Sparus aurata). Fish were fed either a control (CRTL) diet or the postbiotic-supplemented diet (VP) for 62 days. At the end of the feeding trial, a lipopolysaccharide (LPS) challenge was conducted to evaluate the immune response in fish. Histological analysis revealed a healthy mucosa in both groups, though fish fed the VP diet reduced fold height and mucosal layer thickness, alongside a significant increase in goblet cells. Microbiota profiling indicated higher alpha diversity and significant shifts in community composition in the VP group, including enrichment of potentially beneficial genera (Pseudomonas, Sphingomonas) and depletion of opportunistic taxa (Enterococcus, Stenotrophomonas). After the feeding trial, fish fed the VP diet exhibited downregulation of pro-inflammatory markers (tnfα, cox2). Following LPS challenge, cdh1—a key epithelial adhesion protein required for maintaining intestinal barrier integrity—expression was upregulated significantly in the VP group, suggesting enhanced epithelial resilience. These findings demonstrate that dietary fortification with V. proteolyticus-derived postbiotics supports mucosal health as well as modulates the intestinal microbiota and immune responses in gilthead seabream juveniles, offering a promising strategy for functional aquafeed development in sustainable aquaculture.